Penilaian Keterampilan Berbicara Dalam Pembelajaran Bahasa Indonesia Sebagai Bahasa Asing - Nandaliana Indratayana, Ni Wayan; Simpen, I Wayan; Sedeng, I Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): September 2016, 2016)
This article entitled Penilaian Keterampilan Berbicara dalam Pembelajaran Bahasa Indonesia sebagai Bahasa Asing . The aim of this research is to assess learners’ speaking skill in learning Indonesian language after an active learning process had been done that motivates the learners to actively involved, thus the learners can dominate the learning activity and can achieve the basic competency which contained in the lesson plan. The main theory of this research is a rubric design theory proposed by Airasian (2005). The data was collected by using observation and test methods. The techniques used in this articles are check list, written test, and spoken test. The result of this research showed that 80% of the learners actively involved and the aim of learning activity was attained. The learners’ achievement of grammar comprehension is 60% and the comprehension of learning topics that were given in active learning process is 85%. Some factors that obstructed the learners in both aspects mentioned above are the inability of the learners in differentiating and comparing the grammar of their mother language and the Indonesian grammar, the learners’ activities and schedules that made them unable to attend the whole ten meetings before the assessment process by using check list technique, written and spoken test was done.
Keywords: active learning, check list, rating scale, and assessment rubric